Acrylate-vinyl chloride copolymer paste resin and preparation method thereof
The polyacrylate-vinyl chloride copolypaste resin is formed through the seed emulsion polymerization process, which solves the problem of poor mechanical properties of polyvinyl chloride, achieves good compatibility and cost-effectiveness with polyvinyl chloride, and provides high-performance increase Tough effect.
Patent Information
- Application Number
- CN202310780950.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-06-29
AI Technical Summary
Polyvinyl chloride paste resin has poor mechanical properties during processing and requires the addition of expensive additives to improve performance, but poor compatibility leads to increased costs and poor results.
The seed emulsion polymerization process is used to form a polyacrylate-vinyl chloride copolypaste resin. The emulsion with a core-shell structure is formed by copolymerizing the polyacrylate seed latex and vinyl chloride monomer. It has good weather resistance and fire resistance, and is optimized for the formulation. and process to obtain high-performance copolypaste resin.
The obtained copolypaste resin has good compatibility with polyvinyl chloride and is cheap. It can effectively improve the mechanical properties of polyvinyl chloride and has a significant toughening effect, replacing the existing chlorinated polyethylene and acrylate copolymer products.
Smart Images

Figure BDA0004310805950000041 
Figure BDA0004310805950000051 
Figure BDA0004310805950000131
Abstract
Description
Technical Field
[0001] The invention belongs to the field of paste resins, and in particular relates to an acrylate-vinyl chloride copolymer paste resin and a preparation method thereof. Background Art
[0002] PVC paste resin is usually made into plastisol for further processing. Plastisol can obtain PVC plastic products only through heating process. It is mainly used in the production of gloves, artificial leather, coated cloth, flooring, conveyor belts, wallpaper, signs, shoes, toys, etc.
[0003] PVC has poor thermal stability and mechanical properties. Pure rigid PVC is a hard and brittle material. The plasticizer in soft PVC is highly mobile and prone to breakage during use. In order to increase mechanical properties during the processing of PVC, expensive additives such as acrylic copolymers and chlorinated polyethylene need to be added, which increases the cost of PVC finished products. In addition, due to the poor compatibility of acrylic copolymers and chlorinated polyethylene with PVC, the actual effect is not ideal. Summary of the invention
[0004] In order to solve the problems mentioned in the above background technology, the present invention provides an acrylate-vinyl chloride copolymer paste resin, comprising the following raw materials in parts by mass: 2500-7500 parts of deionized water, 2500-7500 parts of polyacrylate seed latex, 2500-7500 parts of vinyl chloride monomer, 5-15 parts of initiator, 1-2 parts of EDTA, 350-400 parts of emulsifier I, 3-7 parts of bleaching powder, 100-300 parts of sodium bicarbonate with a mass fraction of 25%, 0.1-0.5 parts of ferrous sulfate, 4-8 parts of defoaming agent, and 30-50 parts of sodium hydroxide with a mass fraction of 10%.
[0005] Preferably, the polyacrylate seed latex comprises the following raw materials in parts by weight: 6000-7000 parts of deionized water, 500-700 parts of emulsifier, 3000-5000 parts of butyl acrylate, 200-300 parts of methyl methacrylate, 50-150 parts of acrylic acid, 100-150 parts of hydroxyethyl acrylate, 30-40 parts of initiator, 40-60 parts of 10% mass fraction of sodium hydroxide, 3-7 parts of ammonium bicarbonate, 4-8 parts of defoamer, and 4-8 parts of bactericide.
[0006] Preferably, the emulsifier includes emulsifier I, emulsifier S and emulsifier A, the emulsifier I is sodium dodecylbenzene sulfonate, the emulsifier S is sodium dodecyl diphenyl ether sulfonate, and the emulsifier A is sodium 2-hydroxy-3-allyloxypropane sulfonate;
[0007] The initiator is any one of potassium persulfate, sodium persulfate, and ammonium persulfate;
[0008] The defoamer is a mineral oil defoamer;
[0009] The bactericide is thiazolinone.
[0010] Preferably, the preparation process of the polyacrylate seed latex is:
[0011] Preparation of pre-emulsion: add deionized water into the pre-emulsification kettle, start stirring, add emulsifier S, emulsifier A and more than 60% of emulsifier I into the pre-emulsification kettle, stir until the solution becomes transparent, then add butyl acrylate, methyl methacrylate, acrylic acid, hydroxyvinyl acrylate into the pre-emulsification kettle, stir and emulsify to form a stable pre-emulsion, and set aside;
[0012] Preparation of latex initiator solution: add deionized water, initiator and ammonium bicarbonate into the latex initiator dropping tank, stir until the solution becomes transparent, and set aside;
[0013] Polymerization: spray the anti-scaling agent from the top of the condenser outside the polymerization kettle, then add deionized water to the polymerization kettle, start stirring, add the remaining emulsifier I to the polymerization kettle, heat to 75-85°C, add less than 10% of pre-emulsion liquid and less than 20% of latex initiator solution, control the polymerization reaction temperature to 80-90°C, carry out polymerization reaction, form a white emulsion with blue light in the polymerization kettle, add the remaining pre-emulsion liquid and 70%-80% of latex initiator solution dropwise to the polymerization kettle, control the dropping time to 1-4h, the reaction temperature to 80-90°C, add the remaining latex initiator solution to the polymerization kettle after the dropping reaction is completed, and keep the polymerization warm for 0.5-2h, and the keeping temperature of the polymerization kettle to 80-90°C;
[0014] Post-treatment: After the polymerization kettle is heated, the temperature is lowered to below 40°C, the pH value of the emulsion is adjusted to 7-8 with 10% sodium hydroxide solution, a defoamer and a bactericide are added to the polymerization kettle, and the material is filtered with a 180-mesh screen.
[0015] Preferably, the weight ratio of the polyacrylate seed latex to the vinyl chloride monomer is 1:1.
[0016] The present invention also provides a method for preparing an acrylate-vinyl chloride copolymer paste resin, wherein the preparation process of the copolymer paste resin is as follows:
[0017] Preparation of copolymerization initiator solution: Add deionized water and initiator sodium persulfate into the copolymerization initiator tank, stir until the solution becomes transparent, and set aside;
[0018] Preparation of copolymer emulsion: Add deionized water and emulsifier I into the copolymer emulsifier tank, stir until the solution becomes transparent, and set aside;
[0019] Copolymerization: spray the anti-scaling agent from the top of the condenser outside the copolymerization kettle, then add deionized water and polyacrylate seed latex into the copolymerization kettle, stir evenly, add 10% by mass of sodium hydroxide to adjust the pH value to 8-9, add bleaching powder, ferrous sulfate, EDTA and 25% by mass of sodium bicarbonate, then vacuum deoxidize, the vacuum degree is not less than -0.08MPa;
[0020] Raise the temperature to 40-60°C, add vinyl chloride monomer, drop copolymerization initiator solution, control the polymerization temperature at 50-60°C, control the polymerization reaction pressure at 0.5-1MPa, and after the polymerization reaction for 20-40min, drop copolymerization emulsion;
[0021] After the polymerization pressure drops, raise the temperature to 60-80°C, continue the reaction for 30-50min, add a defoaming agent, evacuate, lower the temperature to below 40°C, discharge the material, and dry.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention relies on a mature polyvinyl chloride paste resin production process, first forms polyacrylic acid latex by seed emulsion polymerization, then copolymerizes to form an emulsion with a core-shell structure with polyacrylate as the core and polyvinyl chloride as the shell, the emulsion has weather resistance and intrinsic fire resistance, and finally dries to form a polyacrylate-vinyl chloride copolymer paste resin. The resin has good compatibility with polyvinyl chloride and is cheap. It can be used as an additive to improve the mechanical properties of polyvinyl chloride, has a good toughening effect, and can replace chlorinated polyethylene and acrylate copolymer products currently used in the market.
[0024] 2. The copolymer paste resin obtained by the formula and process of the present invention has excellent properties, wherein the viscosity can reach 1604mPa.s, the tensile strength can reach 45.4MPa, the elongation at break can reach 465%, and the glass transition temperature can reach 55°C. DETAILED DESCRIPTION
[0025] Unless otherwise specified, the reagents used in the present invention are all commercially available, and the parts taken are all by mass.
[0026] In the present invention, the emulsifier I is sodium dodecylbenzene sulfonate;
[0027] Emulsifier S is sodium dodecyl diphenyl ether sulfonate;
[0028] Emulsifier A is sodium 2-hydroxy-3-allyloxypropane sulfonate.
[0029] Main reaction principle
[0030] Preparation of polyacrylate seed emulsion
[0031]
[0032] Preparation of Acrylate-Vinyl Chloride Copolymer Paste Resin
[0033]
[0034] Preparation Example 1
[0035] The preparation process of polyacrylate seed latex is:
[0036] Preparation of pre-emulsion: add 3900 parts of deionized water into the pre-emulsification kettle, start stirring, add 50 parts of emulsifier S, 50 parts of emulsifier A and 375 parts of emulsifier I into the pre-emulsification kettle, stir until the solution becomes transparent, then add 4000 parts of butyl acrylate, 250 parts of methyl methacrylate, 100 parts of acrylic acid and 125 parts of hydroxyvinyl acrylate into the pre-emulsification kettle, stir and emulsify to form a stable pre-emulsion, and set aside;
[0037] Preparation of latex initiator solution: add 1510 parts of deionized water, 35 parts of potassium persulfate, and 5 parts of ammonium bicarbonate into a latex initiator dropping tank, stir until the solution becomes transparent, and set aside;
[0038] Polymerization: spray the anti-scaling agent from the top of the condenser outside the polymerization kettle, then add 1000 parts of deionized water at 80°C to the polymerization kettle, start stirring, add the remaining 125 parts of emulsifier I to the polymerization kettle, raise the temperature to 80°C, add 4.5% pre-emulsion (corresponding to 400 parts) and 13% latex initiator solution (corresponding to 200 parts), control the polymerization reaction temperature to 84-86°C, carry out the polymerization reaction for 30min, a white emulsion with blue light is formed in the polymerization kettle, add the remaining pre-emulsion and 77% latex initiator solution (corresponding to 1200 parts) dropwise to the polymerization kettle, control the dropping time to 2.5-3h, the reaction temperature to 82-84°C, add the remaining latex initiator solution to the polymerization kettle after the dropping reaction is completed, and keep the polymerization warm for 1h. The keeping temperature of the polymerization kettle is 86-88°C;
[0039] Post-treatment: After the polymerization kettle is insulated, the temperature is lowered to below 40°C, the pH value of the emulsion is adjusted to 7-7.5 with 10% sodium hydroxide solution, 6 parts of defoamer and 6 parts of bactericide are added to the polymerization kettle, and the material is filtered with a 180-mesh screen.
[0040] According to the preparation process of polyacrylate seed latex in this example, the particle size of the seeds obtained is 77.4 nm and the pH value is 7.5.
[0041] Preparation Example 2
[0042] The difference between this embodiment and embodiment 1 is "emulsifier S 100 parts, emulsifier A 50 parts, emulsifier I 375 parts", and the rest is exactly the same as preparation example 1.
[0043] According to the preparation process of polyacrylate seed latex in this example, the particle size of the seeds obtained is 81.5 nm and the pH value is 7.2.
[0044] Preparation Example 3
[0045] The difference between this embodiment and embodiment 1 is "50 parts of emulsifier S, 100 parts of emulsifier A, 375 parts of emulsifier I", and the rest is exactly the same as preparation example 1.
[0046] According to the preparation process of polyacrylate seed latex in this example, the particle size of the seeds obtained is 79.6 nm and the pH value is 7.4.
[0047] Preparation Example 4
[0048] The difference between this embodiment and embodiment 1 is "emulsifier S 100 parts, emulsifier A 100 parts, emulsifier I 375 parts", and the rest is exactly the same as preparation example 1.
[0049] According to the preparation process of polyacrylate seed latex in this example, the particle size of the seeds obtained is: 74.4nm; pH value: 7.3.
[0050] Preparation Example 5
[0051] The difference between this embodiment and embodiment 1 is "50 parts of emulsifier S, 50 parts of emulsifier A, 275 parts of emulsifier I", and the rest is exactly the same as preparation example 1.
[0052] According to the preparation process of polyacrylate seed latex in this example, the particle size of the seeds obtained is 76.3 nm and the pH value is 7.2.
[0053] Preparation Example 6
[0054] The difference between this example and Example 1 is "50 parts of emulsifier S, 50 parts of emulsifier A, 475 parts of emulsifier I", and the rest is exactly the same as Preparation Example 1.
[0055] According to the preparation process of polyacrylate seed latex in this example, the particle size of the seeds obtained is 79.9 nm and the pH value is 7.3.
[0056] Preparation Example 7
[0057] The difference between this embodiment and embodiment 1 is that "emulsifier S 50 parts, emulsifier A 50 parts, emulsifier I 425 parts"; the rest is exactly the same as in preparation example 1.
[0058] According to the preparation process of polyacrylate seed latex in this example, the particle size of the seeds obtained is 73.4 nm and the pH value is 7.1.
[0059] Preparation Example 8
[0060] The preparation process of polyacrylate seed latex is:
[0061] Preparation of pre-emulsion: add 3500 parts of deionized water into the pre-emulsification kettle, start stirring, add 50 parts of emulsifier S, 50 parts of emulsifier A and 300 parts of emulsifier I into the pre-emulsification kettle, stir until the solution becomes transparent, then add 3000 parts of butyl acrylate, 200 parts of methyl methacrylate, 50 parts of acrylic acid and 100 parts of hydroxyvinyl acrylate into the pre-emulsification kettle, stir and emulsify to form a stable pre-emulsion, and set aside;
[0062] Preparation of latex initiator solution: add 1500 parts of deionized water, 30 parts of potassium persulfate and 3 parts of ammonium bicarbonate into a latex initiator dropping tank, stir until the solution becomes transparent, and set aside;
[0063] Polymerization: spray anti-scaling agent from the top of the condenser outside the polymerization kettle, then add 1000 parts of deionized water at 80°C to the polymerization kettle, start stirring, add the remaining 100 parts of emulsifier I to the polymerization kettle, raise the temperature to 80°C, add 10% pre-emulsion and 20% latex initiator solution, control the polymerization reaction temperature to 84-86°C, carry out polymerization reaction for 30min, a white emulsion with blue light is formed in the polymerization kettle, add the remaining pre-emulsion and 70% latex initiator solution dropwise to the polymerization kettle, control the dropping time to 2.5-3h, the reaction temperature to 82-84°C, add the remaining latex initiator solution to the polymerization kettle after the dropping reaction is completed, and keep the polymerization warm for 1h, with the keeping temperature of the polymerization kettle at 86-88°C;
[0064] Post-treatment: After the polymerization kettle is heated, the temperature is lowered to below 40°C, the pH value of the emulsion is adjusted to 7-7.5 with 10% sodium hydroxide solution, 4 parts of defoamer and 4 parts of bactericide are added to the polymerization kettle, and the material is filtered with a 180-mesh screen.
[0065] According to the preparation process of polyacrylate seed latex in this example, the particle size of the seeds obtained is 72.1 nm and the pH value is 7.5.
[0066] Preparation Example 9
[0067] The preparation process of polyacrylate seed latex is:
[0068] Preparation of pre-emulsion: add 4500 parts of deionized water into the pre-emulsification kettle, start stirring, add 50 parts of emulsifier S, 50 parts of emulsifier A and 400 parts of emulsifier I into the pre-emulsification kettle, stir until the solution becomes transparent, then add 5000 parts of butyl acrylate, 300 parts of methyl methacrylate, 150 parts of acrylic acid and 150 parts of hydroxyvinyl acrylate into the pre-emulsification kettle, stir and emulsify to form a stable pre-emulsion, which is set aside;
[0069] Preparation of latex initiator solution: add 1500 parts of deionized water, 40 parts of potassium persulfate, and 7 parts of ammonium bicarbonate into a latex initiator dropping tank, stir until the solution becomes transparent, and set aside;
[0070] Polymerization: spray the anti-scaling agent from the top of the condenser outside the polymerization kettle, then add 1000 parts of deionized water at 80°C to the polymerization kettle, start stirring, add the remaining 200 parts of emulsifier I to the polymerization kettle, raise the temperature to 80°C, add 10% pre-emulsion and 20% latex initiator solution, control the polymerization reaction temperature to 84-86°C, carry out the polymerization reaction for 30min, a white emulsion with blue light is formed in the polymerization kettle, add the remaining pre-emulsion and 70% latex initiator solution dropwise to the polymerization kettle, control the dropping time to 2.5-3h, the reaction temperature to 82-84°C, add the remaining latex initiator solution to the polymerization kettle after the dropping reaction is completed, and keep the polymerization warm for 1h, with the keeping temperature of the polymerization kettle at 86-88°C;
[0071] Post-treatment: After the polymerization kettle is insulated, the temperature is lowered to below 40°C, the pH value of the emulsion is adjusted to 7-7.5 with 10% sodium hydroxide solution, 8 parts of defoamer and 8 parts of bactericide are added to the polymerization kettle, and the material is filtered with a 180-mesh screen.
[0072] According to the preparation process of polyacrylate seed latex in this example, the particle size of the seeds obtained is 85.3 nm and the pH value is 7.2.
[0073] Example 1
[0074] The preparation process of copolymer paste resin is:
[0075] Preparation of copolymerization initiator solution: Add 1000 parts of deionized water and 10 parts of potassium persulfate into a copolymerization initiator tank, stir until the solution becomes transparent, and set aside;
[0076] Preparation of copolymer emulsion: Add 1000 parts of deionized water and 375 parts of emulsifier I into the copolymer emulsifier tank, stir until the solution becomes transparent, and set aside;
[0077] Copolymerization: spray the anti-scaling agent from the top of the condenser outside the copolymerization kettle, then add 5000 parts of deionized water and 5000 parts of the polyacrylate seed latex obtained in Preparation Example 1 to the copolymerization kettle, stir evenly, add 10% sodium hydroxide to adjust the pH value to 8-9, add 5 parts of bleaching powder, 0.3 parts of ferrous sulfate, 1.5 parts of EDTA and 200 parts of 25% by mass of ammonium bicarbonate, then vacuum deoxidize, and the vacuum degree is not less than -0.08MPa;
[0078] The temperature was raised to 50°C, 5000 parts of vinyl chloride monomer were added, and the copolymerization initiator solution was added dropwise. The polymerization temperature was controlled at 54°C, and the polymerization reaction pressure was controlled at 0.78 MPa. After the polymerization reaction lasted for 30 minutes, the copolymerization emulsion was added dropwise.
[0079] After the polymerization pressure drops, raise the temperature to 70°C, continue the reaction for 40 min, add a defoaming agent, evacuate, lower the temperature to below 40°C, discharge the material, and dry.
[0080] Example 2
[0081] The difference between this embodiment and embodiment 1 is that “5000 parts of polyacrylate seed latex obtained in preparation example 2”, and the rest is exactly the same as embodiment 1.
[0082] Example 3
[0083] The difference between this embodiment and embodiment 1 is that “5000 parts of polyacrylate seed latex obtained in preparation example 3”, and the rest is exactly the same as embodiment 1.
[0084] Example 4
[0085] The difference between this embodiment and embodiment 1 is that “5000 parts of polyacrylate seed latex obtained in preparation example 4”, and the rest is exactly the same as embodiment 1.
[0086] Example 5
[0087] The difference between this embodiment and embodiment 1 is that “5000 parts of polyacrylate seed latex obtained in preparation example 5”, and the rest is exactly the same as embodiment 1.
[0088] Example 6
[0089] The difference between this embodiment and embodiment 1 is that “5000 parts of polyacrylate seed latex obtained in Preparation Example 6”, and the rest is exactly the same as embodiment 1.
[0090] Example 7
[0091] The difference between this embodiment and embodiment 1 is that “5000 parts of polyacrylate seed latex obtained in Preparation Example 7”, and the rest is exactly the same as embodiment 1.
[0092] Comparative Example 1
[0093] The preparation process of paste resin is:
[0094] Preparation of initiator solution: Add 1000 parts of deionized water and 10 parts of potassium persulfate into the initiator tank, stir until the solution becomes transparent, and set aside;
[0095] Preparation of emulsion: Add 1000 parts of deionized water and 375 parts of emulsifier I into an emulsifier tank, stir until the solution becomes transparent, and set aside;
[0096] Polymerization: spray the anti-scaling agent from the top of the condenser outside the polymerization kettle, then add 9732 parts of deionized water, 28.4 parts of emulsifier S, 28.4 parts of emulsifier A, and 210.4 parts of emulsifier I into the polymerization kettle, stir evenly, add 10% sodium hydroxide to adjust the pH value to 8-9, add 5 parts of bleaching powder, 0.3 parts of ferrous sulfate, 1.5 parts of EDTA and 200 parts of 25% ammonium bicarbonate by mass, then vacuum deoxidize, and the vacuum degree is not less than -0.08MPa;
[0097] The temperature was raised to 50°C, 5000 parts of vinyl chloride monomer were added, the initiator solution was added dropwise, the polymerization temperature was controlled at 54°C, the polymerization reaction pressure was controlled at 0.78 MPa, and after the polymerization reaction lasted for 30 min, the emulsion was added dropwise;
[0098] After the polymerization pressure drops, raise the temperature to 70°C, continue the reaction for 40 min, add a defoaming agent, evacuate, lower the temperature to below 40°C, discharge the material, and dry.
[0099] Results and Testing
[0100] 1. Viscosity test of copolymer paste resin
[0101] Test method: Take 10g of the copolymer paste resin prepared in Examples 1-7 and the paste resin of Comparative Example 1 respectively, add 6g of plasticizer (dioctyl phthalate) to make a paste, and test the viscosity by a rotary viscometer at room temperature (25°C). The results are shown in Table 1.
[0102] Table 1
[0103] project Viscosity (mPa.s) Example 1 1604 Example 2 2134 Example 3 1941 Example 4 2073 Example 5 2256 Example 6 2341 Example 7 2152 Comparative Example 1 2865
[0104] It can be seen from Table 1 that the viscosity of the copolymer paste resins prepared in the embodiments of the present invention is below 2500 at room temperature (25° C.), and the lowest viscosity is in Embodiment 1, which is 1604.
[0105] 2. Mechanical properties test of copolymer paste resin
[0106] Test method: Take 10g of the copolymer paste resin prepared in Examples 1-7 and the paste resin of Comparative Example 1, respectively, add 6g of plasticizer (dioctyl phthalate) to make a paste, plasticize at 180°C for 5min, and obtain a sample with a thickness of 0.25mm. Test the tensile strength and elongation at break by a tensile testing machine at room temperature (25°C), and the tensile rate is 50mm / min. The results are shown in Table 2.
[0107] Table 2
[0108] project Tensile strength(MPa) Elongation at break % Example 1 45.4 465 Example 2 37.1 398 Example 3 38.2 374 Example 4 36.8 399 Example 5 37.5 385 Example 6 34.1 401 Example 7 36.8 367 Comparative Example 1 24.2 265
[0109] It can be seen from Table 2 that the tensile strength of the copolymer paste resins prepared in the embodiments of the present invention is above 30 at room temperature (25°C), among which Example 1 has the highest tensile strength of 45.4; the elongation at break of the copolymer paste resins is above 350 at room temperature (25°C), among which Example 10 has the highest elongation at break of 465.
[0110] 3. Thermal stability test
[0111] Test method: Take 10g of the copolymer paste resin prepared in Examples 1-7 and the paste resin of Comparative Example 1, add 6g of plasticizer (dioctyl phthalate) to make a paste, plasticize at 180°C for 5min, and obtain a sample with a thickness of 0.25mm. Measure the glass transition temperature by a thermogravimetric analyzer. The results are shown in Table 3.
[0112] Table 3
[0113]
[0114]
[0115] It can be seen from Table 3 that the glass transition temperatures of the copolymer paste resins prepared in the embodiments of the present invention are all between 45-65, which is 81 as compared to that in Comparative Example 1, thereby improving the toughness of the product.
[0116] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing an acrylate-vinyl chloride copolymer paste resin, It is characterized in that The following steps are involved: Preparation of copolymerization initiator solution: Add 1000 parts of deionized water and 10 parts of potassium persulfate into a copolymerization initiator tank, stir until the solution becomes transparent, and set aside; Preparation of copolymer emulsion: Add 1000 parts of deionized water and 375 parts of sodium dodecylbenzene sulfonate into the copolymer emulsifier tank, stir until the solution becomes transparent, and set aside; Copolymerization: spray the anti-scaling agent from the top of the condenser outside the copolymerization kettle, then add 5000 parts of deionized water and 5000 parts of polyacrylate seed latex into the copolymerization kettle, stir evenly, add 10% sodium hydroxide to adjust the pH value to 8-9, add 5 parts of bleaching powder, 0.3 parts of ferrous sulfate, 1.5 parts of EDTA and 200 parts of 25% ammonium bicarbonate by mass, then vacuum deoxidize, and the vacuum degree is not less than -0.08MPa; The temperature was raised to 50°C, 5000 parts of vinyl chloride monomer were added, and the copolymerization initiator solution was added dropwise. The polymerization temperature was controlled at 54°C, and the polymerization reaction pressure was controlled at 0.78 MPa. After the polymerization reaction lasted for 30 minutes, the copolymerization emulsion was added dropwise. When the polymerization pressure drops, raise the temperature to 70°C, continue the reaction for 40 minutes, add a defoamer, evacuate, lower the temperature to below 40°C, discharge and dry; The preparation process of polyacrylate seed latex is: Preparation of pre-emulsion: add 3900 parts of deionized water into the pre-emulsification kettle, start stirring, add 50 parts of sodium dodecyl diphenyl ether sulfonate, 50 parts of sodium 2-hydroxy-3-allyloxypropane sulfonate and 375 parts of sodium dodecylbenzene sulfonate into the pre-emulsification kettle, stir until the solution becomes transparent, then add 4000 parts of butyl acrylate, 250 parts of methyl methacrylate, 100 parts of acrylic acid and 125 parts of hydroxyvinyl acrylate into the pre-emulsification kettle, stir and emulsify to form a stable pre-emulsion, and set aside; Preparation of latex initiator solution: add 1510 parts of deionized water, 35 parts of potassium persulfate, and 5 parts of ammonium bicarbonate into a latex initiator dropping tank, stir until the solution becomes transparent, and set aside; Polymerization: spray the anti-scaling agent from the top of the condenser outside the polymerization kettle, then add 1000 parts of deionized water at 80°C to the polymerization kettle, start stirring, add the remaining 125 parts of sodium dodecylbenzene sulfonate to the polymerization kettle, heat to 80°C, add 4.5% pre-emulsion and 13% latex initiator solution, control the polymerization reaction temperature to 84-86°C, carry out the polymerization reaction for 30 minutes, a white emulsion with blue light is formed in the polymerization kettle, add the remaining pre-emulsion and 77% latex initiator solution dropwise to the polymerization kettle, control the dropping time to 2.5-3h, the reaction temperature to 82-84°C, add the remaining latex initiator solution to the polymerization kettle after the dropping reaction is completed, and keep the polymerization warm for 1h, with the keeping temperature of the polymerization kettle at 86-88°C; Post-treatment: After the polymerization kettle is insulated, the temperature is lowered to below 40°C, the pH value of the emulsion is adjusted to 7-7.5 with 10% sodium hydroxide solution, 6 parts of defoamer and 6 parts of bactericide are added to the polymerization kettle, and the material is filtered with a 180-mesh screen.
